Cyprus Institute of Research Promotion (IPE) titled ‘Linguistic & Genetic factors in the prognosis of children with late onset of expressive language’, funded by the Cyprus Institute of Research Promotion. - (:unkn) unknown (My University, 2026)
RESEARCH EXPERIENCE